On Hölder continuity of solutions of the Beltrami equations - Ryazanov, V.; Salimov, R.; Sevost’yanov, E. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.5We consider the problem of local behavior of solutions of the Beltrami equations in arbitrary domains.  We have found sufficient conditions for the complex coefficient of the Beltrami equation guaranteeing the existence of its Hölder continuous solution in an arbitrary domain.  These results can be used in the boundary-value problems for the Beltrami equation, as well as in the hydromechanics of strongly anisotropic and inhomogeneous media.